Nanomedicines for Near-Infrared Fluorescent Lifetime-Based Bioimaging - Lian, Xianhui; Wei, Ming-Yuan; Ma, Qiang (Frontiers in Bioengineering and Biotechnology, 2019)
Nanomedicines refer to the application of nanotechnology in disease diagnosis, treatment, and monitoring. Bioimaging provides crucial biological information for disease diagnosis and treatment monitoring. Fluorescent bioimaging shows the advantages of good contract and a vast variety of signal readouts, and yet suffers from imaging depth due to the background noise from the autofluorescence of tissue and light scattering. Near-infrared fluorescent life-time bioimaging (NIR- FLTB) suppress such background noises and significantly improve signal-to-background ratio. This article gives an overview of recent advances in NIR- FLTB using organic compounds and nanomaterials as contrast agent (CA). The advantages and disadvantages of each CA are discussed in detail. We survey relevant reports about NIR- FLTB in recent years and summarize important findings or progresses. In addition, emerging hybrid bioimaging techniques are introduced, such as ultrasound-modulated FLTB. The challenges and an outlook for NIR- FLTB development are discussed at the end, aiming to provide references and inspire new ideas for future nanomedicine development.